Water security in northern Morocco: natural difficulties, water requirements, technical measures, and the most important state strategies - the case of the Al Hoceima region - Amar ABATOUY,; Driss DAOUI,; El Bid Mustapha, (International Journal of Scientific Research and Innovative Studies, 2026)
Water is very important in the Al Hoceima region of Northern Morocco and underpins the region's stability, population growth, and social, economic, and environmental development. Al Hoceima, along with the rest of North Morocco, has been receiving heavy rainfall over the last two decades. Al Hoceima, however, has been receiving much less rain than it has over the last two decades. Current climate change poses obstacles that affect almost every domain: Al Hoceima's natural wealth has been stressed, and in Al Hoceima, the water has literally reversed. Rainfall has been very extreme in Al Hoceima (the last 20+ year time span shows that annually it has been as low as 300-1000mm and for the rest of the Kingdom, Al Hoceima persists* to use a water management strategy, of its own, as it is the case for the rest of the Kingdom. For this reason, the issue of Al Hoceima is particularly relevant, given the lack of rainfall and water stress. This particularly applies to Northern Morocco and the region of Al Hoceima, which recognises the decreasing availability of water. This is particularly the case during the time of the realisation of the impacts of climate change and even the localised impacts of climate change, which include, among others, industrial water use and the resultant and sustained high demand attributed to population increase, which also affects the water-deficient resources due to over-reliance on dam water, coupled with water-consuming farming practices. In this regard, the above factors necessitated the formulation of numerous questions, particularly regarding the water resources of the Northern region of Morocco, and Al-Hoceima in particular. We then pose a secondary question: how effectively do the water policies in place promote water governance and regulate water use? Keywords: water resources - northern Morocco - Al Hoceima city - rainfall - climate change. Received Date: February 22, 2026 Accepted Date: March 14, 2026 Published Date: April 02, 2026 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/611